'To the Extremes of Asian Sensibility': Balinese Performances at the 1931 International Colonial Exhibition. Issue 2 (1st September 2022) - Ladeira, Juliana Coelho de Souza
Abstract: This article proposes a comprehensive and detailed approach to the reception of the Balinese performances and the performers' stay at the International Colonial Exhibition of 1931, held in Vincennes, France. Thus, it analyses French sources, such as the daily press, specialised and literary magazines, photographs, films and sound recordings. As one of the most acknowledged attractions of the Exhibition, the Balinese group appeared extensively in the press. This ensemble of documents allowed us to understand that their performances' favourable reception contributed considerably to creating a positive impression of Dutch colonisation and the progressive inclusion of Bali in the world's cartography.